Heroic failure and the British - Barczewski, Stephanie L. (Yale University Press, 2016)
In this work, historian Stephanie Barczewski argues that Britain's embrace of heroic failure initially helped to gloss over the moral ambiguities of imperial expansion. Later, it became a strategy for coming to terms with diminishment and loss. Filled with compelling, moving, and often humourous stories from history, Barczewski's survey offers a fresh way of thinking about the continuing legacy of empire in British culture today.